Information Disseminated by Spore 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Niels Louwaars, CPRO DLO, Wageninen, The Netherlands: 'Thanks for arranging publication in SPORE of our article on the services of CPRO-DLO in the field of plant variety protection (the plant breeders' rights). We received some valuable feedback, as...